2020
DOI: 10.1177/1479164120952321
|View full text |Cite
|
Sign up to set email alerts
|

Estimated glucose disposal rate demographics and clinical characteristics of young adults with type 1 diabetes mellitus: A cross-sectional pilot study

Abstract: Background: Estimated glucose disposal rate (eGDR) is a practical measure of Insulin Resistance (IR) which can be easily incorporated into clinical practice. We profiled eGDR in younger adults with type 1 diabetes mellitus (T1DM) by their demographic and clinical characteristics. Methods: In this single centre study, medical records of TIDM were assessed and eGDR tertiles correlated with demographic and clinical variables. Results: Of 175 T1DM individuals, 108 (61.7%) were males. Mean age (±SD) was 22.0 ± 1.6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…Furthermore, we found significant interactions between eGDR and sex, age and anti-diabetes/hypertension drugs on risk of CVD. However, significant associations between eGDR with risk of CVD were observed in all subgroups, which was consistent with previous reported studies [ 29 31 ]. The present study provides a more valid appraisal of the relationship between eGDR and CVD, stroke and cardiac events.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, we found significant interactions between eGDR and sex, age and anti-diabetes/hypertension drugs on risk of CVD. However, significant associations between eGDR with risk of CVD were observed in all subgroups, which was consistent with previous reported studies [ 29 31 ]. The present study provides a more valid appraisal of the relationship between eGDR and CVD, stroke and cardiac events.…”
Section: Discussionsupporting
confidence: 93%
“…This was similar to study conducted by Mihaela L. Bîcu et al who found that obese patients had lower eGDR in comparison with lean subjects (19). Higher insulin doses and an increase in the rate of hypoglycemia may be possible causes for development of obesity and subsequent insulin resistance in T1DM cases (20).…”
Section: Discussionsupporting
confidence: 90%
“…Apart from micro-and macro-vascular complications, events like acute coronary syndrome are related to abnormal eGDR [7]. Also, individuals with type 1 diabetes mellitus (T1DM) and low eGDR have altered cholesterol and triglycerides [8]. These studies substantiate the significance of eGDR as an easy alternative tool for determining insulin resistance and to predict metabolic dysfunctions in a large population.…”
Section: Introductionmentioning
confidence: 61%